CIVIL KEYSTROKES: EXAMINING ANONYMITY, POLITENESS, AND CIVILITY IN ONLINE NEWSPAPER FORUMS - Dillon, Kelly P; Neo, Rachel L.; Seely, Natalee (AoIR Selected Papers of Internet Research, 2015)
Online news discussion forums have become popular virtual spaces for public discourse, especially as more newspapers bring their publications online. Computer- mediated communication theories, such as the social identity model of deindivudating effects (Spears & Lea, 1994), suggest the anonymity afforded by online platforms leads to a deindividuation of the individuals involved, leading to less civility and politeness. The current study examines the role of anonymity within the CMC setting of online news comment forums and whether commentary posted by anonymous users contains more incivility and impoliteness than Facebook identified users. Comments left to two Associated Press articles, political and non-political, were collected from four major Midwest newspapers’ websites. Results suggest individuals commenting from anonymous handles are less civil and less polite in their comments than those individuals commenting through Facebook profiles. Political news stories garnered more comments that were less civil and less polite than non-political stories. Future research is necessary to determine the implications of incivility in online discussion and its effects on democracy and productive public discourse.